Teaching in a Web-based Distance Learning Environment - Мудра, Олена; Mudra, Olena (MDPC Publishing, 2021)
Building online course takes a tremendous amount of time and effort. We’ve created a syllabus, selected a textbook, wrote learning objectives, recorded lectures, developed learning objects, designed course activities, and carefully planned out our assignments. But without proper planning and design, a large portion of our course may have to be redeveloped for the next offering. If planned and designed properly, however, an online course can be offered relatively intact from semester to semester. As with traditional courses, online courses will need a change here and a tweak there, but major reconstruction can be largely avoided. The article includes possible answers to potential problems.
Building online course takes a tremendous amount of time and effort. We’ve created a syllabus, selected a textbook, wrote learning objectives, recorded lectures, developed learning objects, designed course activities, and carefully planned out our assignments. But without proper planning and design, a large portion of our course may have to be redeveloped for the next offering. If planned and designed properly, however, an online course can be offered relatively intact from semester to semester. As with traditional courses, online courses will need a change here and a tweak there, but major reconstruction can be largely avoided. The article includes possible answers to potential problems.